Assessment of specimen fixation in a surgical pathology service. Issue 6 (June 1992) - Start, R D; Cross, S S; Smith, J H
Abstract : The quality of specimen fixation was examined within a routine diagnostic histopathology service. For each specimen the adequacy of fixation was assessed and the transit time between operating theatre and the laboratory was measured. Preliminary fixation was found to be inadequate in 25% of specimens and some form of manipulation to assist fixation was required in 36% of specimens. The mean transit time was 22 (SD 10.7) hours. Specimen fixation and transport are additional factors to consider in quality assurance of histopathology.